THE EFFECT OF INNOVATION PRODUCT AND HALAL LABELIZATION ON BUYING REPURCHASE SPECIAL FOOD IN BLITAR CITY - Liestya Padmawidjaja; Rama Septriduta Surya Negara; Christian Herdinata (UNUSA Press, 2021)
Increased growth of food and beverage businesses that grow above the Gross Domestic Product (GDP) in the Blitar City area from year to year. Making food and beverage business people must strive to maintain their competitive edge in order to maintain their business amid the many competitors that continue to emerge, especially in this study, namely the typical food product business of the City of Blitar Cang-Jo, Uceng Tho Siti, and Abon Lele Mekarsari. The purpose of this study was to determine and analyze the effect of product innovation and halal label on repurchase interest in Blitar City. The method used in this research is quantitative. The data analysis method used is multiple linear regression using SPSS software. with a research sample of 100 respondents obtained by the technique of calculating the number of indicators of all variables at times 10. Data collection was carried out using hypothesis testing and statistical tests. The results of this study are product innovation and halal labeling have a significant effect on repurchase special food in Blitar City.